PENINGKATAN PANGSA PASAR PADA BISNIS KEDAI KOPI MELALUI CUSTOMER LOYALTY - IVANALIE, RAISA; SUTRISNO, NUNO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
The purpose of this study is to analyze the influence of Sensory Experience, Emotional Experience, Social Experience and Service Quality on Customer Loyalty through Customer Satisfaction among consumers of Kulo coffee shops in Bekasi City. This study uses primary data obtained through distributing questionnaires. Data analysis was carried out quantitatively and used a causal research design. The sampling for this research was purposive sampling using 254 respondents. This research data was processed using WarpPLS 8.0 software. The results of this research prove that sensory, emotional, social, service and satisfaction influence loyalty. It is hoped that this research can help provide input or suggestions for the coffee shop business, especially the kulo coffee shop which is the object of this research, so that it can increase its market share in the coffee shop business in Indonesia.